Kinetic aspects of malachite deposition on marble from copper lactate solutions - Gogol, Daniil B.; Rozhkovoy, Ivan E.; Sadyrbekov, Danyar T.; Aldabergenova, Saule K.; Makasheva, Astra M. (Comptes Rendus. Chimie)
Experiments were conducted to study the formation of copper minerals on carbonate material (marble) from lactate solutions. Main kinetic parameters were estimated from the curves of copper ions deposition. The reaction rate constant is $4.19 \times 10^{-6}~\text{s}^{-1}$ and the effective diffusion coefficient is $1.39 \times 10^{-12}~\text{m}^2/\text{s}$ at room temperature (25 °C). IR spectra of sediments show good agreement with natural samples of malachite and azurite (Spassk deposit, Central Kazakhstan). The results show the possibility of using organic complexing agents for intensifying the processes of secondary mineral formation of copper carbonate minerals (malachite and azurite) to prevent the dissipation of heavy metal ions in soluble forms from poor deposits and dumps during their remediation.